2000
DOI: 10.1254/jjp.84.163
|View full text |Cite
|
Sign up to set email alerts
|

The Scopolamine-Induced Impairment of Spatial Cognition Parallels the Acetylcholine Release in the Ventral Hippocampus in Rats

Abstract: We investigated the relationship between the induction of spatial cognition impairment in the 8-arm radial maze task and regional changes (ventral hippocampus (VH), dorsal hippocampus, frontal cortex, and basolateral amygdala nucleus) in brain acetylcholine (ACh) release using microdialysis in rats treated with muscarinic (M) receptor antagonists. In a behavioral study, two M1 antagonists, scopolamine (0.5 mg/kg, i.p. and 20 microg, i.c.v.) and pirenzepine (80 microg, i.c.v.), but not an M2 antagonist, AF-DX11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 29 publications
4
33
0
1
Order By: Relevance
“…in the scopolamine-induced impairment of spatial memory in the 8-arm radial maze, in agreement with our previous report (23). Moreover, we analyzed THC-and scopolamine-induced response patterns regarding arm choice by a CCD camera connected to a personal computer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…in the scopolamine-induced impairment of spatial memory in the 8-arm radial maze, in agreement with our previous report (23). Moreover, we analyzed THC-and scopolamine-induced response patterns regarding arm choice by a CCD camera connected to a personal computer.…”
Section: Discussionsupporting
confidence: 90%
“…We recently reported that the scopolamine-induced impairment of spatial memory in an 8-arm radial maze closely paralleled the change in acetylcholine release in the ventral hippocampus using microdialysis techniques (23). Therefore, scopolamine was used for comparison with the THC-induced impairment of working memory.…”
mentioning
confidence: 99%
“…In addition, we provide parallel evidence that fluoxetine's anxiolytic action may be mediated through a decrease of aversive stimulus-and aversive memory-evoked increases in cholinergic neurotransmission through M1 muscarinic receptors in the hippocampus, although this evidence is strictly circumstantial and needs to be further investigated in future studies. It seems unlikely that injections of pirenzepine induced an anxiolytic effect by reducing overall ACh efflux since previous studies have reported that pirenzepine either increases or does not affect ACh efflux (Douglas et al, 2001;Mishima et al, 2000). Therefore, the observed effect seems to be solely attributed to a blockade of the M1 receptors.…”
Section: Discussionmentioning
confidence: 87%
“…This accumulation seemed to be due to a increase in the specific binding of The most important finding is that an increase in [ 3 H] QNB binding caused by irradiation can only be detected in the intact brain. In the cholinergic system, such as choline acethyltransferase and ACh receptor, it plays important roles in learning and spatial cognition (18)(19)(20). We indicated that a transitional increase of mACh receptor in vivo binding in the early phase at 24 hrs after irradiated with the proton beam at a dose of 30 Gy.…”
Section: Ach Receptor Binding Assaymentioning
confidence: 86%